Effects of cisapride on gastric emptying of oil and aqueous meal components, hunger, and fullness. Issue 3 (March 1996) - Jones, K L; Horowitz, M; Carney, B I; Sun, W M; Chatterton, B E
Abstract : To evaluate the effects of cisapride on gastric emptying of extracellular fat and hunger and fullness 10 volunteers consumed a meal consisting of 60 ml technectium-99m (99mTc)-V-thiocyanate labelled olive oil and 290 ml indium-113m (113mIn) labelled soup after taking cisapride (10 mg four times daily orally) and placebo, each for four days, in randomised, double blind fashion. Gastric emptying was quantified scintigraphically. Hunger and fullness before and after the meal were evaluated using visual analogue scales. Cisapride accelerated gastric emptying of oil and aqueous components by reducing the lag phase mean (SEM) (20.3 (7.0) min v 40.7 (4.1) min (p < 0.05) for oil and 4.1 (2.5) min v 10.0 (3.1) min (p < 0.05) for aqueous). Cisapride had no effect on the post-lag emptying rate of oil. Treatment with cisapride was associated with reduced retention of oil in the proximal stomach (p < 0.05). Subjects were more hungry before ingestion of the meal while receiving cisapride (6.7 (0.9) v 3.9 (0.7), p < 0.001). The scores for hunger at 120 and 180 minutes were inversely related to gastric emptying of oil on both cisapride (r > -0.62, p < 0.05) and placebo (r > -0.86, p < 0.001). Fullness increased after the meal while receiving placebo (p < 0.01), but not cisapride and postprandial fullness was less with cisapride at (30 min; 0.4 (0.3) v 3.3 (1.0), p < 0.05). With placebo, but not cisapride, the score for fullness at 15 minutes was inversely related to emptying of the aqueous phase (r = 0.68, p < 0.05). These results show that in normal volunteers after ingestion of an oil/aqueous meal: (a) postprandial hunger is inversely related to gastric emptying of oil, while fullness is inversely related to gastric emptying of the aqueous phase, (b) cisapride affects the intragastric distribution and accelerates gastric emptying of both oil and aqueous meal components, and (c) cisapride increases preprandial hunger and reduces postprandial fullness.